PERKEMBANGAN SAINS DAN TEKNOLOGI DALAM PERSPEKTIF AGAMA - Nia Anugrah Ramadhani Safitri; Sallsanabilla Ramadani; Latifah (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
The development of science and technology has become a dominant force shaping modern civilization. However, this progress cannot be separated from the ethical, moral, and spiritual dimensions emphasized by religion. This article aims to explore the relationship between science, technology, and religion from an integrative perspective, focusing on how religious values guide and give meaning to scientific advancement. The research method used is library research with philosophical and theological approaches. The results show that religions such as Islam, Christianity, Hinduism, and Buddhism view science as part of humanity’s search for divine truth. In Islam, for instance, knowledge (‘ilm) is regarded as a form of worship and moral responsibility. Technology is also seen as a means for public welfare rather than domination over nature. This study emphasizes the importance of integrating science and religion to achieve ethical and civilized progress. Thus, technological advancement should be directed toward human welfare, ecological balance, and spiritual development.